Mobile payments: Main trends in the retail industry - Tatjana Apanasevic (International Telecommunications Society (ITS), 2014)
The main objective of the ongoing study is to investigate obstacles and driving forces affecting organization adoption of innovation. In order to that an example of the mobile payments applied in the Swedish retail industry has been used. The main analyzed factors are: adopter characteristics, supplier marketing activity, perceived innovation characteristics, social network, and environmental influences. The analysis of case study findings helped to estimate some common trends in the adoption of mobile payment services by retailers. As a result, the analyzed factors were categorized as obstacles or driving forces to adoption of the mobile payments.
Keywords: 330; Mobile Payment Services; Organizational Acceptance of Technology; Service Adoption; Mobile payments; Mobile payment services; Retail; Merchants